Alvar Aalto & Helsinki - Helsinki (2008)
"Alvar Aalto and Helsinki" explores the profound influence of the Finnish architect Alvar Aalto on the urban and architectural development of Helsinki. The book examines Aalto's key projects, his design philosophy, and his role in shaping the modern identity of Helsinki through innovative architecture and urban planning. It offers insights into Aalto's integration of functionality, aesthetics, and humanistic considerations within the context of the Finnish capital.
Keywords: Finnish Architecture; Architecture, Alvar Aalto; Urban Planning -- Modernism